The role of Tiktok as content marketing to maintain brand engagement - Wiwarottami, Anggi Septyavi; Widyatama , Rendra (COMMICAST, 2023)
In the digital era, social media platforms such as TikTok have become increasingly important in company marketing strategies. This research will focus attention on the use of TikTok as a tool to build and maintain customer engagement or brand engagement. The Originote, a local skincare brand from Indonesia which was founded in 2018, has felt the impact of the rapid development of technology and social media. One of the Originote products has not previously received much attention from the public and has had big challenges in building brand awareness. So this research was conducted with the main aim of investigating the role of social media on TikTok as an effective content marketing tool for maintaining brand engagement levels, especially for flagship products from The Originote. The research used descriptive qualitative methods for seven months from January 2023-July 2023, focusing on social media TikTok @theoriginote. Data was collected through content analysis and triangulation from different sources, including written notes, literature, journals, articles and the internet related to research. The research results show that Tiktok's role in marketing activities through video content to maintain brand engagement has a great influence on sales traffic. The brand engagement carried out by The Originote regarding the Hyalucera Moisturizer product received a positive response from followers of the Tiktok application, comments column, testimonials through video content, sharing video content of the Hyalucera Moisturizer product and reviews that can help convince consumers to buy this product.